SISTEM KONTROL SMART AHU MENGGUNAKAN PLC DAN HMI DI RUANG OPERASI RSUD SITI FATIMAH PALEMBANG - Masri Surya Maulana; Marfin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
"Smart AHU Control System using PLC and HMI in Operating Room" is a system that utilizes PLC (Programmable Logic Controller) and HMI (Human-Machine Interface) technology to automatically control temperature and humidity in the operating room. This system can monitor the conditions in the operating room in real-time and provide feedback to the operator through the HMI interface. By using this system, the operator can easily adjust the temperature and humidity in the operating room according to the desired needs and conditions, ensuring the comfort and safety of patients and medical staff during the operation. This system also has a self-diagnosis feature that can detect and provide warning for problems that may occur in the system, helping to ensure optimal performance and reduce downtime. The error value of XY-MD02 sensor for temperature is 0.81% and the error value for humidity is 2.29%.